A Comparison of Sexual Arousal in Men Exposed to Visual Stimuli With and Without Facial Blurring. (September 2020) - Rosetti, Leah; Curry, Susan; Murphy, Lisa; Bradford, John B.; Fedoroff, J. Paul
The role of the facial images in arousal and attraction has been examined before but never via penile plethysmography (PPG). This retrospective chart review aimed to determine the significance and magnitude of differences in arousal measured by PPG in 1, 000 men exposed to slide stimuli with or without facial blurring in subjects of various ages. Arousal in response to blurred stimuli was significantly higher than nonanonymized stimuli with modest effect sizes for slides across age and gender categories. Facial blurring increased differences in arousal between adults and adolescents with a modest effect size. Our findings support the use of facial blurring to further protect the anonymity of models and limit the ethical and legal challenges of using slide stimuli with child models.